Regulation of molybdate transport by Clostridium pasteurianum. - Elliott, B B (1976)
The regulation of the molybdate (MoO42-) transport activity of Clostridium pasteurianum has been studied by observing the effects of NH3, carbamyl phosphate, MoO42-, and chloramphenicol on the ability of cells to take up MoO42-. Compared with cells fixing N2, cells grown in the presence of 1 mM NH3 are greater than 95% repressed for MoO42- transport. Uptake activity begins to increase just before NH exhaustion (under Ar or N2) and continues to increase throughout the lag period as cells shift from NH3-growing to N2-fixing conditions. When cells are shifted from N2-fixing to NH3-growing conditions the transport activity per fixed number of cells decreases by increase of bells in absence of transport synthesis. Carbamyl phosphate (greater than or equal to 15 mM) but not NH3 inhibits 58% of the in vitro uptake activity. When 1 mM carbamyl phosphate is added just before the exhaustion of NH3, the transport activity, measured 2 h later, is 100% repressed. Cells grown in the presence of high MoO42- (1mM) are 80% repressed for MoO42- transport. Synthesis of the MoO42- transport system is also completely stopped when chloramphenicol (300 mug/ml) is added just before the exhaustion oNH 3 from the medium. These findings demonstrate that the ability of cells to transport MoO42- is dependent upon new protein synthesis and can be repressed by high levels of substrate. The regulation of MoO42- uptake by NH3 or carbamyl phosphate closely parallels the regulation of nitrogenase activity. Activity of neither nitrogenase component (Fe protein or MoFe protein) was detected even 3 h after the exhaustion of the NH3 if either MoO42- was absent or if WO42- was present in place of MoO42-. The duration of the diauxic lag increases with decreasing concentration of MoO42- in the medium. If no MoO42- is present the lag continues indefinitely. If MoO42- is added late in the lag period, growth under N2-fixing conditions resumes but only after a normal induction period.